EVALUASI PROGRAM PENGUATAN PENDIDIKAN KARAKTER TERINTEGRASI MATA PELAJARAN MATEMATIKA DI SDN 64/III KERINCI - Rilla Gina Gunawan; Ambiyar; Aziz, Ishak (Cerdas Proklamator, 2022)
Education is not only a process of delivering factual information but also instilling moral and ethical principles in its students. The purpose of this study is to ascertain the impact and influence of the integrated character education strengthening program in mathematics at SDN 64/III Kerinci and to evaluate the factors that contribute to the success or failure of the program. Methods: This research is evaluative with a qualitative approach. This research was conducted at the 64/III Kerinci Elementary School. The results of the study show that: 1) The application of integrated character education in mathematics at SDN 64/III Kerinci begins with the planning, implementation, and assessment stages. The teacher's role in character education has not been fully realized in terms of design, implementation, and assessment. 2) The implementation of the character education strengthening program increases the workload for teachers, especially in terms of attitude evaluation, which has a negative impact on teachers but a positive impact on students in terms of achievement and behavior. 3) Limited facilities and infrastructure, a lack of trained educators, limited access to information, as well as student attitudes and mentalities, are all obstacles to the implementation of integrated character education with mathematics subjects.